Penerimaan bukan Islam terhadap proses islamisasi di Malaysia - Abdull Rahman Mahmood,; Kamaruddin Hj Salleh,; Ahmad Sunawari Long,; Faudzinaim Badaruddin, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2009)
Malaysia is a multi-religious country. It has been clearly spelled out in the Constitution that Islam is the religion of the Federation. However, it should be noted that other religious are free to be expressed in their own ways as well. Histories showed that Islam developed since the 1970s and ignite many colourful changes throughout the Islamisation processes that have been evolved. This writing is trying to review the non-Muslims’ understanding and acceptance towards the Islamisation process in Malaysia. This review is based on the library researches and references from the diverse sources. Generally, the non-Muslims in Malaysia are not really understand and accepting the Islam as a way of life.